H2O2 and CH3OOH (MHP) in the Remote Atmosphere: 2. Physical and Chemical Controls. Issue 6 (18th March 2022) - Allen, Hannah M.; Bates, Kelvin H.; Crounse, John D.; Kim, Michelle J.; Teng, Alexander P.; Ray, Eric A.; Wennberg, Paul O.
Abstract: Hydrogen peroxide (H2 O2 ) and methyl hydroperoxide (MHP, CH3 OOH) serve as HO x (OH and HO2 radicals) reservoirs and therefore as useful tracers of HO x chemistry. Both hydroperoxides were measured during the 2016–2018 Atmospheric Tomography Mission as part of a global survey of the remote troposphere over the Pacific and Atlantic Ocean basins conducted using the NASA DC‐8 aircraft. To assess the relative contributions of chemical and physical processes to the global hydroperoxide budget and their impact on atmospheric oxidation potential, we compare the observations with two models, a diurnal steady‐state photochemical box model and the global chemical transport model Goddard Earth Observing System (GEOS)‐Chem. We find that the models systematically under‐predict H2 O2 by 5%–20% and over‐predict MHP by 40%–50% relative to measurements. In the marine boundary layer, over‐predictions of H2 O2 in a photochemical box model are used to estimate H2 O2 boundary‐layer mean deposition velocities of 1.0–1.32 cm s −1, depending on season; this process contributes to up to 5%–10% of HO x loss in this region. In the upper troposphere and lower stratosphere, MHP is under‐predicted and H2 O2 is over‐predicted by a factor of 2–3 on average. The differences between the observations and predictions are associated with recent convection: MHP is under‐estimated and H2 O2 is over‐estimated in air parcels that have experienced recent convective influence. Plain Language Summary: Hydrogen peroxide (H2 O2 ) and methyl hydroperoxide (MHP, CH3 OOH) in the atmosphere can act as reservoirs for one of the main drivers of atmospheric chemistry, HO x (HO x  = OH and HO2 ). Both H2 O2 and MHP were measured during the 2016–2018 Atmospheric Tomography Mission (ATom), which investigated the atmosphere over the oceans far from direct human influence. The measurements are compared to two types of models to assess our understanding of the chemical and physical processes that control their abundance. We find that these models consistently predict H2 O2 to be lower and MHP to be higher than was measured during ATom. We use the discrepancy between the model and the measurements to investigate the role of deposition (removal of compounds from the Earth's atmosphere due to interactions with surfaces and with liquid water) on H2 O2 in the lowest portion of atmosphere and the role of convection (vertical transport during storms and other meteorological events) on MHP between 6 and 12 km altitudes. Key Points: The global distribution of H2 O2 and methyl hydroperoxide (MHP) reflects the influence of photochemistry, convective transport, and wet and dry deposition Deposition of H2 O2 plays a key role in removing HOx within the marine boundary layer MHP in the upper troposphere is highly sensitive to convective transport and the Goddard Earth Observing System (GEOS)‐Chem model substantially underestimates MHP advective mass fluxes